2014
DOI: 10.1038/srep07167
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of wnt4a gene and evidence for positive selection in half-smooth tongue sole (Cynoglossus semilaevis)

Abstract: Wnt4 gene plays a role in developmental processes in mammals. However, little is known regarding its function in teleosts. We cloned and characterized the full-length half-smooth tongue sole (Cynoglossus semilaevis) wnt4a gene (CS-wnt4a). CS-wnt4a cDNA was 1746 bp in length encoding 353aa. CS-wnt4a expression level was highest in the testis, and gradually increased in the developing gonads until 1 year of age. In situ hybridization revealed that CS-wnt4a expression level was highest in stage II oocytes and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 58 publications
(95 reference statements)
4
22
0
Order By: Relevance
“…The 2ΔLnL value of the accD gene is 25.91159 with a p-value of LRT is 0.0000024. The positively selected sites detected in the present study may drive the accD protein-coding gene allowing the occupation of diverse habitats [34,35].…”
Section: Discussionmentioning
confidence: 70%
“…The 2ΔLnL value of the accD gene is 25.91159 with a p-value of LRT is 0.0000024. The positively selected sites detected in the present study may drive the accD protein-coding gene allowing the occupation of diverse habitats [34,35].…”
Section: Discussionmentioning
confidence: 70%
“…Tissue distribution pattern of wnt5 and wnt4 showed their abundance in the ovary indicating a potential influence of these correlates as observed in other species (Vainio et al 1991, Oreal et al 2002, Pailhoux et al 2002, Jaaskelainen et al 2010, and in contrast to these, ovarypredominant function was not observed in rainbow trout (Nicol et al 2012). The levels of wnt4, which seems to be homologous to its paralog, wnt4a observed in other species shows contradictory expression pattern by being predominant in ovary unlike Cynoglossus semilaevis wnt4a (Hu et al 2014). Although the levels of expression are comparatively less in tissues other than ovary and kidney, the presence of wnt transcripts suggests their role in development as that of other teleosts (Matsui et al 2005).…”
Section: :1mentioning
confidence: 71%
“…In humans, it is required for oocyte selection, follicle formation and maturation (Boyer et al 2010b, Jaaskelainen et al 2010, Prunskaite-Hyyryläinen et al 2014. The precise functions of this gene in teleosts are not well explored in reproduction although it is identified in several teleosts such as zebrafish (Ungar et al 1995), rainbow trout (Nicol et al 2012), medaka (Yokoi et al 2003), half-smooth tongue sole (Hu et al 2014), black porgy (Wu & Chang 2009) and hermaphrodite and orange-spotted grouper (Chen et al 2015). Two paralogs of this gene were reported in zebrafish, medaka and half-smooth tongue sole with variant functions during development.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcription (RT) was performed at 30°C for 10 min followed by 42°C for 60 min in a total volume of 20 μL consisting of 1 μg total RNA, 1×M‐MLV buffer, 0.5 mM each dNTP, 1.25 μM random primers, and 200 UM‐MLV Reverse Transcriptase (Takara, Dalian, People's Republic of China). The PCR reaction mixture and conditions were performed as described (Hu et al., ). PCR was performed as follows: five cycles of 94°C for 30 sec and 72°C for 3 min; five cycles of 94°C for 30 sec, 70°C for 30 sec, and 72°C for 3 min; then 27 cycles of 94°C for 30 sec, 68°C for 30 sec, and 72°C for 3 min.…”
Section: Methodsmentioning
confidence: 99%